2021
DOI: 10.1002/pmic.202000295
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of the search engine, Bolt, to decrease search time and increase peptide identifications in hydroxyl radical protein footprinting‐based workflows

Abstract: Hydroxyl radical protein footprinting (HRPF) utilizes hydroxyl radicals to covalently modify solvent exposed regions of proteins. When coupled with mass spectrometry, HRPF can provide insightful information on protein structural changes including inside cells. However, the complex mixture of proteins and modifications makes identification a complicated task. To search all of the HRPF-induced modification combinations across the full proteome, requires substantial computational power and still can take days to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The workflow SS_H–II, with the most PSMs only took 101.5 min, four times faster than MS_Var (Figure B). Our hybrid method (72 mzML files in less than 2 h) is also considerably faster than previous cloud-based high-performance search methods for FPOP data (96 mzML files in 64 h) …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The workflow SS_H–II, with the most PSMs only took 101.5 min, four times faster than MS_Var (Figure B). Our hybrid method (72 mzML files in less than 2 h) is also considerably faster than previous cloud-based high-performance search methods for FPOP data (96 mzML files in 64 h) …”
Section: Resultsmentioning
confidence: 94%
“…FPOP can modify 19 of the 20 amino acids, meaning that the number of allowed modification sites on a peptide is nearly the same as the length of the peptide. Furthermore, many residues have several different modifications that can be induced by FPOP, , resulting in a total of 51 modification-residue combinations, which further increases the number of possible configurations for a peptide sequence. The result is that search methods that are effective for searching modified peptides in typical proteomics contexts struggle to achieve sufficient speed and sensitivity for FPOP searches.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this, Rinas et al developed a multilevel strategy in the search algorithm Sequest to increase throughput . Recently, it was demonstrated that the novel cloud-based search engine Bolt outperformed the Sequest-based multilevel strategy in both computational time and number of identifications . A comparison of Sequest and Bolt for IC-FPOP showed that Bolt identified a 1.5-fold greater number of modified peptides in 64 h of computational time compared to 203 h for Sequest, thus increasing throughput and the amount of structural information.…”
Section: Discussionmentioning
confidence: 99%
“…200 Recently, it was demonstrated that the novel cloud-based search engine Bolt outperformed the Sequest-based multilevel strategy in both computational time and number of identifications. 201 A comparison of Sequest and Bolt for IC-FPOP showed that Bolt identified a 1.5-fold greater number of modified peptides in 64 h of computational time compared to 203 h for Sequest, thus increasing throughput and the amount of structural information. Finally, the recently developed FoxWare protein footprinting software has been successful in quantification of HRPF modifications.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, MSbased methods are well-suited to handle the heterogeneity arising from presence of post-translational modifications and exhibit sufficient sensitivity, sample-throughput, and dynamic range to enable largescale systematic measurements of proteomes (Benesch et al, 2007;Kondrat et al, 2015;Meier et al, 2015;Meier et al, 2020). Moreover, traditional MS-based methods can provide indirect structural information via measurements of mass-to-charge ratios of labelled or digested protein components (Chea et al, 2021). Furthermore, hybrid ion mobility/mass spectrometry (IM/MS, Figure 1A) methods characterize atomic structures of proteins and protein complexes via their orientationally-averaged collision cross sections.…”
Section: Introductionmentioning
confidence: 99%